“Calculadora de sustentabilidade” aplicado à avaliação de indicadores de desenvolvimento rural sustentável, utilizando a metodologia MADERUS - Feitosa Filho, Luiz Alves (2023)
The concept of sustainable development implies meeting present needs without compromising the possibilities of future generations, avoiding the exhaustion of natural resources. Based on this idea, we sought to develop a user-friendly tool, i.e. an App, that incorporated the MADERUS (Methodology for Evaluating Sustainable Rural Development) approach, especially for evaluating Family Farm Production Units. The aim was to develop and validate a digital tool (App) for assessing Sustainability Indicators in production units. The approach adopted involved a case study carried out on site, combining bibliographical research with primary and secondary data to assess the level of sustainability of the units. Ten production units were selected for the study, in which a questionnaire with 53 questions was applied in printed form and another in the app. The response time between the "Sustainability Calculator" app and the traditional method was compared, and the results indicated that the average time spent using the app was 17.21 minutes, while the traditional method took an average of 36.65 minutes, representing a reduction of 19.14 minutes in the response time using the app, in relation to the tabulation time in the traditional system it took 18.65 minutes and in the app the results are in real time. The results showed that the sustainability calculator offers benefits in its use, both because it eliminates the need to use paper and because it significantly saves time in the process of collecting and processing the results.